Nio films for electrochromic windows / Siti Zairyn Fakurol Rodzi and Dr. Yusairie Mohd - Fakurol Rodzi, Siti Zairyn; Mohd, Yusairie (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
The purpose of this study was to prepare nickel (II) oxide (NiO) thin films for electrochromic materials application (smart windows) using electrodeposition method. By adjusting the electrodeposition conditions, two different types of NO films were produced; smooth and porous films. The films exhibit electrochromic effect (their optical transmittance changes from transparent to grey colour) by applying electrical voltage. The results showed that the smooth NiO film has excellent chemical stability, good switching colour, good adhesion on ITO substrate and high stability in electrolyte. The preparation of NiO films using this technique can be considered as the most convenient and cost-effective process. The NiO films have high potential for development of smart windows that are the forefront of emerging energy-saving advances in building technologies.